1995
DOI: 10.1084/jem.181.5.1805
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines increase human hemopoietic cell adhesiveness by activation of very late antigen (VLA)-4 and VLA-5 integrins.

Abstract: Sunlln~l.l-yCytokines are known to be important regulators of normal hemopoiesis, acting in concert with components of the bone marrow microenvironment. Interactions with this microenvironment are known to regulate the proliferation, differentiation, and homing of hemopoietic progenitor (CD34 +) cells. Adhesive interactions with the extracellular matrix retain CD34 + cells in close proximity to cytokines, but may also provide important costimulatory signals. Thus, the functional states of adhesion receptors ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
183
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(189 citation statements)
references
References 55 publications
5
183
1
Order By: Relevance
“…6,14 BM CD34 + cells may acquire the capacity to circulate by changing the pattern of Discussion adhesion molecule expression following GM-CSF administration. However, GM-CSF is known to upregulate specific This study was designed to evaluate differences in the expression of adhesion molecules on CD34 + cells in periphadhesion molecules including those in the integrin family on PCs, monocytes and endothelial cells, [23][24][25] although eral blood leukapheresis products (GM-CSF-mobilized) in comparison to CD34 + cells in steady-state BM products.…”
Section: Enrichment Of Cd34 + Cellsmentioning
confidence: 99%
“…6,14 BM CD34 + cells may acquire the capacity to circulate by changing the pattern of Discussion adhesion molecule expression following GM-CSF administration. However, GM-CSF is known to upregulate specific This study was designed to evaluate differences in the expression of adhesion molecules on CD34 + cells in periphadhesion molecules including those in the integrin family on PCs, monocytes and endothelial cells, [23][24][25] although eral blood leukapheresis products (GM-CSF-mobilized) in comparison to CD34 + cells in steady-state BM products.…”
Section: Enrichment Of Cd34 + Cellsmentioning
confidence: 99%
“…SCF promotes the survival (Domen and Weissman, 2000), proliferation (Leary et al, 1992;Tsai et al, 1991), mobilization (Fleming et al, 1993) and adhesion (Levesque et al, 1995) of hematopoietic stem cells and their progenitors. The cytokine is also involved in the development and function of other cell lineages, including melanocytes and germ cells (Sette et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Given that FN enhances gene transfer in CML CD34 + HLA-DR + and CD34 + may partially restore the adhesive properties of CML HPC. This notion is supported by recent work by Levesque et al, 48 HLA-DR − cells, serious consideration of clinical gene therapy protocols which include FN-coated culture dishes during prein which they demonstrated that exposure of normal human CD34 + cells to SCF, IL-3 and GM-CSF in combination constimulation and transduction of CML cells, as well as those intended for the treatment of other diseases, is warranted. ferred on these cells an enhanced adherence to FN.…”
Section: Figurementioning
confidence: 83%